Rethinking Racism: Toward Hamka’s (1908-1981) Perspectives in Tafsir al-Azhar - Usman, Abur Hamdi; Zainal Abidin, Salman (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
Racism is an ideological belief that considers one’s race to be more civilized, advanced, intelligent, and moral than others. Race as an ideology, masked as a scientific and natural fact, is frequently used to justify inequality and the domination of one group over another. However, in the teachings of Islam, the concept of the division of people or human beings based on race, gender, skin color, rank, or descent is unacceptable. Currently, a person may comfortably and ignorantly use specific untrue terms to show that they are the ‘chosen race’ preferred by God as an honorable race compared to others. Given the use of race to justify social systems and behaviors are anathemas to Islam, the current article analyses the issue of racism using the views of a famous scholar from Indonesia, Haji Abdul Malik Karim Amrullah, popularly known as Hamka, in his exegetical work Tafsir al-Azhar. Using the content analysis method, this article found that Hamka strongly emphasizes racial unity because humans are descended from one ancestry. In Hamka’s perspective, there is no difference between one or another group of people except taqwa (piety). There is no need to leverage differences but remain aware of the similarities of lineage.